Pengaruh Perhatian Orang Tua Terhadap Prestasi Belajar Siswa Kelas V SD Negeri 2 Brangkal Tahun Pelajaran 2023/2024 - Sri Rahayu; Nela Rofisian; Iswan Riyadi (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This research aims to determine whether there is a positive and significant influence of parental attention on the learning achievement of class V students at Brangkal 2 Elementary School. This is motivated by the problems faced by students in class V of Brangkal State Elementary School 2 during the learning process at school, namely (1) lack of attention from parents, (2) there are students who do not want to study alone at home. This research is quantitative research using an Ex Post Facto approach. The population in this study was all students at Brangkal 2 Elementary School, totaling 152 students. Sampling was carried out using a purposive sampling technique, namely all class V students of Brangkal 2 State Elementary School. The data collection technique in this research uses a questionnaire with a Likert Scale. The data obtained is in the form of questionnaire results and documentation results. The data analysis techniques used are Normality Test, Linearity Test, Simple Linear Regression Test, and Coefficient of Determination. The results of this study show that there is an influence between parental attention and the learning achievement of class V students at Brangkal 2 Elementary School as evidenced by the results of calculating significant values ​​from simple regression calculations with a value of 0.001 which is less than 0.05 and a calculated t value > t table of 3.683 is greater than 1.697, meaning that Ha is accepted and Ho is rejected. So it can be concluded that parental attention influences the learning achievement of class V students at SD Negeri 2 Brangkal.